One-step on-chip microfluidic synthesis of the hybrid capsules using aqueous two-phase system - Daradmare, Sneha; Kim, Jae Seong; Ganguly, Reya; Lee, Chang-Soo (Frontiers in Sensors, 2022)
Hydrogel capsules synthesized by conventional water-in-oil emulsion systems are the less preferred choice for biomedical applications due to the use of oils and surfactants. An aqueous two-phase system (ATPS), which allows the formation of water-in-water emulsion, is considered a green alternative and therefore has been explored a lot for its application in the biomedical field. Herein, we present the synthesis of hydrogel capsules using a set-up consisting of a pneumatic valve integrated with the ATPS microfluidic system. In this arrangement, at first, a pneumatic valve facilitates the generation of the droplets of one aqueous system i.e. sodium alginate (SA) containing dextran solution into another aqueous phase comprising polyethylene glycol solution. The present approach allows good control over droplet generation by tuning the pressure of the pneumatic valve and the flow rates of the core and middle phases. The synthesis of hybrid capsules within the microfluidic device is carried out mainly by using the interfacial complexation of oppositely charged polyelectrolytes, chitosan with SA via electrostatic interactions. The interfacial complexed SA and chitosan hydrogel capsules were collected via the settling collection method, which ensures the retaining of the shape of the hybrid capsules. The morphological properties of as-synthesized droplets and hybrid capsules were examined via optical microscopy. The hydrogel capsules show good encapsulation capability for the magnetic particles. Even though this study mainly focuses on the synthesis part, we anticipate that the proposed approach will enable the encapsulation of cells within the hybrid capsules as well as enhance the cell adhesion on the surface of the hydrogel capsules hence, these hydrogel capsules can find the potent application in the biomedical engineering.